Respostas
respondido por:
4
Explicação passo-a-passo:
a)
log (x. y) = log x + log y
log (x . y) = log 1000 + log 10000
log (x . y) = log 10³ + log 10⁴
log (x . y) = 3 + 4
log (x . y) = 7
b)
log (10000 : 1000) = log 10000 - log 1000
log (10000 : 1000) = log 10⁴ - 10³
log (10000 : 1000) = 4 - 3
log (10000 : 1000) = 1
respondido por:
0
Resposta:
Explicação passo-a-passo:
a)1000.10000=10000000
b)10000:1000=10
Perguntas similares
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás